(untitled) (Research, Society and Development, 2022)
The moment of childbirth is very unique in the life of the pregnant woman, as this experience has always represented a unique and special moment, marked by the transformation of the woman in her new role, that of being a mother, however and some factors can influence her in the choice of delivery route, such as a previous traumatic experience, fears, misinformation, comfort or even recovery, as well as the influence of other people. The objective of the study was to carry out a comparative analysis of the occurrence of normal and cesarean deliveries in Brazil, through an integrative literature review. This is an integrative literature review study, carried out in the Latin American and Caribbean Literature in Health Sciences (LILACS) and National Library of Medicine (PUBMED) databases in the period between 2017 and 2022. that among the deliveries performed in Brazil, the highest prevalence is of cesarean deliveries, observed in regions with greater development and economic power and in women over 35 years old, married and with higher education. It was also noted that the fear of pain was one of the most used criteria in women’s decision for elective cesarean section resources that enable conscious decision-making about the mode of delivery.